Navigating the fulfillment of needs in university students: parenting styles, body perception, and well-being - D’Urso, Giulio; La Marca, Luana; Marzullo, Rossella (Frontiers in Psychology, 2025)
The literature has highlighted the importance of investigating the factors that influence the satisfaction of university students’ basic psychological needs for relatedness, competence, and autonomy. This study, indeed, aims to examine whether parenting style can affect students’ general well-being and attitudes toward their body, and whether these factors, in turn, influence the fulfillment of their basic psychological needs. The sample consisted of 189 university students (177 females and 12 males) who completed a series of self-report questionnaires measuring perceived parenting style (Perceptions of Parents Scales, POPS), body image (Body Appreciation Scale-2, BAS-2), general well-being (Mental Health Continuum–Short Form, MHC–SF), and need satisfaction (Basic Psychological Satisfaction and Frustration Scale, BPNSF). Path analysis revealed that a positive parenting style has a significant positive impact on both body image and overall well-being. Among these two factors, only general well-being significantly predicted the satisfaction of basic psychological needs. Theoretical and clinical implications are discussed.